The fluctuation of exchange rate and its effect on commercial bank performance - Fazli, Sanaurahman; Arian, Ajmal (Journal of Asian Business Strategy, 2025)
The present study examines the effect of exchange rate fluctuation and bank size on the financial performance of top commercial banks of Afghanistan (Azizi Bank, Afghan United Bank, Afghanistan International Bank, Islamic Bank of Afghanistan) for the period from the first quarter of 2016 to the fourth quarter of 2020, where Return on Equity (ROE) is the most important indicator of measuring performance. Using panel data regression estimates spanning across four banking institutions, the evidence reveals that bank size, in the form of the natural logarithm of total assets, exerts a significant and statistically positive impact on ROE, whereas exchange rate fluctuation exhibits a statistically insignificant but positive relationship with profitability. Sufficient diagnostic checks validate the integrity and consistency of the model. These results indicate that bank size is a more fundamental determinant than exchange rate fluctuation with respect to profitability in the banking sector of Afghanistan. The study emphasizes the importance of diversification and expansion strategies in financial institutions in the process of building them into robust and resilient institutions against the influence of a poor economic environment. The conclusions here carry high policy relevance for policymakers and bank chief executives who seek to promote financial stability and sustainable development within Afghanistan’s nascent financial sector.